PENGARUH PRODUK, TARIF SEWA, LOKASI DAN PROMOSI TERHADAP TINGKAT OKUPANSI PASAR TRADISIONAL DI PASAR ENCIK PUAN PERAK KOTA TANJUNGPINANG - Syahril Prayoga; Winata Wira; Firmansyah Kusasi (CV. Denasya Smart Publisher, 2026)
Traditional markets play an important role in the local economy, yet many face declining occupancy post-revitalization. This study analyzes the influence of Product, Rental Rates, Location, and Promotion on the occupancy levels of the Encik Puan Perak Market in Tanjungpinang City. Following a massive 79 billion IDR revitalization, the market only achieved a 12.1% occupancy rate in 2025. This research employs a quantitative descriptive approach with a population of active and illegal traders around the market. A sample of 147 respondents was selected using purposive sampling. Data were analyzed using Multiple Linear Regression via SPSS software. The results indicate that, partially, the variables Product, Rental Rates, and Promotion have a positive and significant impact on occupancy levels. Conversely, the Location variable does not have a significant influence. Simultaneously, all independent variables affect the dependent variable with an explanatory power (Adjusted R Square) of 73.8%. These findings suggest that management should prioritize internal accessibility and intensive promotion over mere geographical location to attract traders.